2017
DOI: 10.1002/pon.4571
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, quality‐of‐life, and symptom clusters in breast cancer: Using Bayesian networks to elucidate complex relationships

Abstract: The Bayesian network identified local structure (eg, fatigue-mood-QoL or sleep-cognition) and possible intervention targets (eg, a sleep intervention to reduce cognitive complaints during chemotherapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
2
37
0
2
Order By: Relevance
“…The pattern of correlations found between PSQI and the cognitive variables suggests that self‐reported sleep quality indices are related to PCI but not to cognitive performance of verbal fluency, attention, executive functioning, or memory, which is congruent with some previous research but contrary to findings from Xu et al who reported that sleep quality was a significant predictor of neuropsychological performance in BCS receiving chemotherapy. The women in our sample performed average to above average on the neuropsychological tests, possibly because they were highly educated and therefore had high cognitive reserve.…”
Section: Discussionsupporting
confidence: 79%
“…The pattern of correlations found between PSQI and the cognitive variables suggests that self‐reported sleep quality indices are related to PCI but not to cognitive performance of verbal fluency, attention, executive functioning, or memory, which is congruent with some previous research but contrary to findings from Xu et al who reported that sleep quality was a significant predictor of neuropsychological performance in BCS receiving chemotherapy. The women in our sample performed average to above average on the neuropsychological tests, possibly because they were highly educated and therefore had high cognitive reserve.…”
Section: Discussionsupporting
confidence: 79%
“…In a cross‐sectional analysis of 1072 breast cancer survivors, approximately 71.7% of patients with severe insomnia reported moderate or greater cognitive difficulties compared with only 20.0% of patients without insomnia 28 . Thus, improving sleep has been identified as a potential management strategy for patients with CRCI 29‐31 …”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant curative therapies are applied in the majority of cases that possibly influence their cognitive functioning and psychological well-being (2)(3)(4)(5). The adverse effects of adjuvant therapies on cognitive functioning including verbal memory (immediate and delayed recall), visuo-spatial memory, executive functioning, attention/concentration, psychomotor speed, verbal fluency, verbal articulation (language skills) may exert profound effects on quality of life (QOL) (6)(7)(8). Chemotherapy-related cognitive deterioration originally named as "chemobrain" is a wellknown phenomenon which includes various chemotherapyinduced deficits and impairments such as decline of verbal memory and psychomotor functioning (3,(9)(10)(11).…”
mentioning
confidence: 99%